Brown adipocyte-derived exosomes in type 2 diabetes mellitus impair endothelial function via regulating intracellular calcium cycle - Ruan, Xiaojie; Zhao, Wei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtherosclerosis is a leading cause of macrovascular complications in type 2 diabetes mellitus (T2DM). Lipid metabolism disorders in T2DM alter exosomal cargos, affecting vascular endothelial cells and impairing vascular endothelium-dependent relaxation.ObjectiveThis study investigates the link between T2DM and atherosclerosis, focusing on adipose tissue-derived exosomes (AT-Exosomes) as key pathogenic factors in T2DM.MethodsAT-exosomes derived from diabetic (C57BLKS-Leprdb/db) and non-diabetic (C57BLKS-Leprdb/+) mice were co-cultured with vascular aorta to evaluate pathogenicity. RNA screening in mouse aortic endothelial cells (MAECs) identified differential genes impacted by T2DM brown adipose tissue (BAT)-derived vs. healthy BAT-derived exosomes.ResultBAT-derived exosomes significantly disrupted endothelium function compared to white adipose tissue (WAT)-derived exosomes. Inositol 1,4,5-trisphosphate receptor type 3 (ITPR3) gene expression in MAECs was significantly reduced in diabetic mice. Functional studies revealed that ITPR3 positively regulates the Ca2+/CAMKII/eNOS signaling pathway to inhibit nitric oxide (NO) release, impairing endothelial relaxation.ConclusionBAT-derived exosomes in T2DM reduce ITPR3 expression in endothelial cells, lowering intracellular Ca2+ and NO production, thereby contributing to vascular endothelium-dependent relaxation dysfunction. Targeting this pathway may offer therapeutic insights for T2DM-associated vascular complications.